Micromanaging the classification of colon cancer. The role of the microRNAome - Vilar, Eduardo (2011)
Recent advances in the understanding of the microRNAome provide further insights into the molecular pathogenesis of colorectal cancer and demonstrate the potential role for miRNAs to distinguish molecular subtypes. The mucosa-adenoma-carcinoma model can now integrate miRNAs into the known genetic alterations that drive the progression of colorectal neoplasia.